Safety and immunogenicity of rabies vaccine (PVRV-WIBP) in healthy Chinese aged 10-50 years old: Randomized, blinded, parallel controlled phase III clinical study - Xiaoyuan Huang; Jing Liang; Lili Huang; Xuanxuan Nian; Wei Chen; Jiayou Zhang; Xiao Xu; Xuan Lin; Yue Wang; Jinrong Shi; Lanxin Jia; Qingliang Li; et al. (Taylor & Francis Group, 2023)
This phase III clinical trial aimed to assess the safety and demonstrate the immunogenicity of a candidate freeze-dried purified Vero cell-based rabies vaccine (PVRV-WIBP) developed for human use. A cohort of 40 participants in stage 1 and 1956 subjects in stage 2 with an age range of 10-50 years were recruited for the phase III clinical trial. For safety analysis in stage 1, 20 participants received either 4-dose or 5-dose regimen of PVRV-WIBP. In stage 2, 1956 subjects were randomly divided into the 5-dose PVRV-WIBP, 5-dose PVRV-LNCD, and 4-dose PVRV-WIBP groups. The serum neutralizing antibody titer against rabies was determined on day 7 or 14 and day 35 or 42. Adverse reactions were recorded for more than 6 months. Most adverse reactions, which were mild and moderate in severity, occurred and resolved within 1 week after each injection in the PVRV-WIBP (4 and 5 doses) and PVRV-LNCD (5 doses) groups. All three groups achieved complete seroconversion 14 days after the initial dose and 14 days after completing the full vaccination schedule, the susceptible subjects in the PVRV-WIBP group (4-dose or 5-dose regimen) displayed higher neutralizing antibody titers against the rabies virus compared to those in the PVRV-LNCD group (5-dose regimen). PVRV-WIBP induced non-inferior immune responses versus PVRV-LNCD as assessed by seroconversion rate. PVRV-WIBP was well tolerated and non-inferior to PVRV-LNCD in healthy individuals aged 10-50 years. The results indicated that PVRV-WIBP (both 4- and 5-dose schedules) could be an alternative to rabies post-exposure prophylaxis.